Analisis Pengaruh Variasi Menu dan Digital Marketing Terhadap Minat Beli Pelanggan Cafe Rumah Pohon Medan - Helmi, Muhammad Muda Mulya; Nst , Amrin Mulia Utama (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine and influence menu variations and digital marketing on the purchase interest of customers of Cafe Rumah Pohon. The research method used is exploratory research, where variables are measured using a Likert scale. Data collection methods were carried out by interview, with a list of questions (questionnaire) and documentation studies. The population in this study were all customers at Cafe Rumah Pohon. totaling 92 people. Sampling using the saturated sampling method or better known as the census. In this study, the population was relatively small, namely 92 people. Data processing used SPSS version 23 software, with descriptive analysis and multiple regression analysis hypothesis testing. The results of the study showed that: (1) partially the menu variation variable affects the purchase interest of Cafe Pohon customers (2) partially the digital marketing variable affects the purchase interest of Cafe Rumah Pohon customers; (3) simultaneously there is a positive and significant influence between the menu variation variable and digital marketing on the purchase interest of Cafe Rumah Pohon customers.